Phosphorus species, fractions, and leaching risk in vermicompost-amended calcareous sandy loam soil - Mahsa Asariha; Mahboubeh Zarabi (International Journal of Recycling of Organic Waste in Agriculture, 2023)
Purpose Organic matter has significant effects on phosphorus (P) retention in soil. Applying vermicompost (VC) as an organic amendment is an eco-friendly approach to increase sustainability in agriculture. There is a high potential of P loss by leaching or surface runoff from coarse-textured soils. Column leaching experiments were conducted to determine the effect of VC on P mobility in a P fertilized sandy loam soil.Method Soil columns were amended with different VC dosages (2% VC, 3% VC, and 5% VC w/w) and leached with distilled water for 31 days. Phosphorus, base cations and anions concentration, EC, and pH were analyzed in leachates and P species, leaching rate, and fractions in amended soils were determined, too.Results The HPO4-2 and MgHPO4 (aq) were the dominant species in the leachates and their highest total concentration was observed in 5% VC-amended columns. Vermicompost increased P leaching and its leaching rate ranged from 0.41 mg kg-1day-1 for control to 0.59 mg kg-1day-1 for 5% VC-amended columns. With increasing VC dosage Res–P, NaOH–P, and KCl–P fractions decreased, but the HCl-P fraction increased.Conclusion Results indicate that the VC with increasing moderately labile P fraction (HCl-P) and HPO4 -2 and MgHPO4 (aq) species can enhance P leaching from sandy loam soil.